Metabolite profiling reveals the metabolic features of the progenies resulting from the low phytic acid rice (Oryza sativa L.) mutant. (July 2021) - Zhou, Chenguang; Zhou, Yaojie; Tan, Yuanyuan; Shu, Qingyao; Li, Youfa; Liu, Jie; Wang, Jing; Shi, Jiyong; Zou, Xiaobo
Abstract: The low phytic acid ( lpa ) rice mutant Os - lpa -XS110-2, exhibiting OsMRP5 mutation-induced metabolic features (i.e. decreased levels of phytic acid and raffinose, and increased levels of amino acids and biogenic amine GABA), was crossed with two commercial rice cultivars. The inferior field emergence rate of the lpa mutant was significantly improved upon cross-breeding. The GC/MS-based metabolomics was utilized to investigate the impact of cross-breeding on the metabolite profiles of the resulting progeny rice grains. Multivariate and univariate analyses showed that in spite of the predominant influence of crossing parent on the metabolite profiles of the progenies, the OsMRP5 mutation-induced metabolite signature, was stably expressed in the lpa mutant progenies over generations. The OsMRP5 lpa rice mutant seeds might be considered valuable genetic resources to develop rice grains with favorable metabolic traits. Graphical abstract: Image 1 Highlights: The agronomic traits of OsMRP5 lpa rice mutant was improved after cross-breeding. The mutation-induced metabolite signature was stably expressed in lpa progenies. The levels of lipids in progenies were increased with ascending generations.